The Radicalization of Brexit Activists - Mason, Clare B.; Winter, David A.; Schmeer, Stefanie; Berrington, Bibi T. J. S. L. (Frontiers in Psychology, 2022)
Brexit activists demonstrating outside the British Houses of Parliament were studied in situ to examine their potential for pro-group extreme behaviour. This involved activists of two polarised, opposing views; those of Leave and Remain. The research engaged concepts linking the different theoretical perspectives of identity fusion and personal construct psychology. The study measured participants’ degree of fusion to their group using a verbal measure. Willingness to undertake extreme acts was assessed in several ways: a measure of willingness to fight for the group, adaptations of the trolley dilemma and questions regarding political violence. Individual construing was examined using repertory grid technique and a semi-structured interview. Results were similar for both Leave and Remain participants. The majority of activists identified as ‘fused’ to their group and, if so, were more likely to undertake hypothetical extreme behaviour compared to those who did not identify as ‘fused’. Repertory grid technique indicated that becoming an activist provided individuals with a clearer and more positive view of themselves. Opposition activists were construed more negatively and extremely than fellow activists, and this construal was associated with an increased willingness to undertake extreme pro-group behaviour. This was consistent with the personal construct model of radicalization and was heightened in those who were ‘fused’. Interview data provided support for the constructivist model and revealed characteristics and concerns of the two groups. Overall, the findings indicate that campaigning organisations contain fused individuals, who are more likely to undertake hypothetical pro-group violence including self-sacrifice. This has broader implications which may be particularly pertinent, given the violent impact of extremist activists around the globe.